The Role of ISCR1-Borne POUT Promoters in the Expression of Antibiotic Resistance Genes - Lallement, Claire; Pasternak, Cécile; Ploy, Marie-Cécile; Jové, Thomas (Frontiers in Microbiology, 2018)
The ISCR1 (Insertion sequence Common Region) element is the most widespread member of the ISCR family, and is frequently present within γ-proteobacteria that occur in clinical settings. ISCR1 is always associated with the 3’Conserved Segment (3’CS) of class 1 integrons. ISCR1 contains outward-oriented promoters POUT, that may contribute to the expression of downstream genes. In ISCR1, there are two POUT promoters named PCR1-1 and PCR1-2. We performed an in silico analysis of all publically available ISCR1 sequences and identified numerous downstream genes that mainly encode antibiotic resistance genes and that are oriented in the same direction as the POUT promoter. Here, we showed that both PCR1-1 and PCR1-2 significantly increase the expression of the downstream genes blaCTX-M-9 and dfrA19. Our data highlight the importance of ISCR1 in the expression of antibiotic resistance genes which may explain why ISCR1 is the most prevalent member of the ISCR family and also why ISCR1 is so frequent in clinical settings. Indeed, ISCR1 gives an advantage to the bacteria for antimicrobial resistance expression.